STUDI DENSITAS LINEAMENT DAN POLA ALIRAN PERMUKAAN DAERAH MANIFESTASI GEOTERMAL DI SEKITAR DANAU - Cyrke A. Bujung (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2020)
North Sulawesi is an area with a complex geological structure because North Sulawesi is located in a collision zone of three plates at once. Therefore, North Sulawesi has geothermal potential which can be used as a power plant. Surface manifestations associated with surface geological structures can be identified based on lineament analysis on remote sensing images. This study aims to identify the geological structure of the surface of the geothermal area based on its lineament density, flow patterns, and surface manifestations. The surface structure was analyzed by lineament density at the surface by the FFD method. This lineament is assumed to be associated with a fracture or fault which in the geothermal area is generally covered by surface manifestations so that it is difficult to identify. These faults and fractures are assumed to be weak areas where the thermal fluid moves so that they can be a clue to the location of the permeable area or reservoir. The results showed that the high density of surface geological structures is associated with the presence of geothermal manifestations on the surface of the Tondano caldera and its surroundings. The manifested area is an area with a dense flow pattern and is a young volcanic rock.